Proto-Eskimo-Aleut */ə/ and the Origin of Aleut Pre-Aspirated Consonants - Alonso de la Fuente, José Andrés (Ediciones Complutense, 2010)
The aim of this paper is to analyze several points of the Aleut historical phonology which up till now had not received enough attention. The programmed agenda comprises: (I) Proto-Eskimo-Aleut */ə/; (II) the pre-aspiration; (III) the Proto-Eskimo-Aleut sequences */-nə-/ and */-ŋə-/, and (IV) Aleut lexicon containing x̣- (γ.-). An ideal understanding of these processes shall help to the reconstruction of the Proto-Aleut language, an issue totally rejected in the specialized literature. El objetivo de este trabajo es analizar ciertos aspectos de la fonologia historica aleuta que previamente no habian recibido suficiente atencion. Estos puntos comprenden: (I) vocal protoesquimalaleuta */ə/, (II) el fenomeno de la preaspiracion, (III) las secuencias protoesquimalesaleutas */-nə-/ y */-ŋə-/, y (IV) lexico aleuta que contiene x̣- (γ.-). La correcta comprension de estos procesos ayudara en la reconstruccion de la etapa lingüística protoaleuta, hasta ahora totalmente ignorada en la bibliografia especializada.